Assessment of common errors and subjective quality of digital panoramic radiographs in a dental institution - Nithin Kumar (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of the study was to determine the incidence of patient preparation and positioning errors during panoramic radiographic imaging and to assess the subjective quality of panoramic radiographs in a sample of records collected from a dental institution. Materials and Methods: The study material was 1000 randomly selected panoramic radiographs obtained from the database of the department of oral and maxillofacial radiology. Patient preparation and positioning errors of the radiographs were evaluated and categorized into nine groups. The sample radiographs were also evaluated for subjective quality according to a three-point quality scale by the National Radiological Protection Board (United Kingdom) as "excellent," "diagnostically acceptable," or "unacceptable." Results: Out of 1000 radiographs evaluated, failure to position the tongue against palate was the most common error at 69.5% and patient movement during radiographic exposure was the least common error at 0.4%. As per the subjective quality ratings, 22.4% of the radiograph had excellent quality, 66.4% were diagnostically acceptable, and 13.2% were unacceptable. Conclusion: The incidence of patient positioning errors in the panoramic radiographs was relatively common. The quality of the diagnostic panoramic radiographs could be improved by better operator education and awareness in relation to patient preparation and positioning.